2018
DOI: 10.1002/14651858.cd011341.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Cyclamen europaeum extract for acute sinusitis

Abstract: The effectiveness of Cyclamen europaeum for people with acute sinusitis is unknown. Although no serious side effects were observed, 50% of participants who received Cyclamen europaeum reported adverse events compared with 24% of those who received placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
4
0
2
Order By: Relevance
“…It is also possible that the immediate irritative effect of CE might have compromised the blinding of treatment in both trials. The Cochrane meta-analysis published in 2018 based on these two trials concluded that the efficacy of CE is unknown, while adverse events including nasal and throat irritation, mild epistaxis, and sneezing were more frequent with CE nasal spray than with placebo (risk ratio [RR]: 2.11; 95% CI 1.35 to 3.29) [30]. This meta-analysis found an overall low risk of selection, performance and detection bias in the two studies included.…”
Section: Ce Versus Placebomentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that the immediate irritative effect of CE might have compromised the blinding of treatment in both trials. The Cochrane meta-analysis published in 2018 based on these two trials concluded that the efficacy of CE is unknown, while adverse events including nasal and throat irritation, mild epistaxis, and sneezing were more frequent with CE nasal spray than with placebo (risk ratio [RR]: 2.11; 95% CI 1.35 to 3.29) [30]. This meta-analysis found an overall low risk of selection, performance and detection bias in the two studies included.…”
Section: Ce Versus Placebomentioning
confidence: 99%
“…This meta-analysis found an overall low risk of selection, performance and detection bias in the two studies included. The authors also emphasized the need for further randomized controlled trials to evaluate the efficacy of this treatment for acute rhinosinusitis [30].…”
Section: Ce Versus Placebomentioning
confidence: 99%
“…Также возможно, что немедленное раздражающее действие цикламена могло поставить под угрозу слепой режим обоих исследований. Кокрановский метаанализ, опубликованный в 2018 г. на основе этих двух исследований, показал, что эффективность цикламена неизвестна, в то время как НЯ, включая раздражение в носу и горле, несильное носовое кровотечение и чиханье, были чаще отмечены при использовании назального спрея цикламена, чем при применении плацебо (относительный риск -ОР 2,11; 95% ДИ 1,35-3,29) [30]. Этот метаанализ показал общий низкий риск систематической ошибки, связанной с отбором, эффективностью и выявлением определенного исхода в двух включенных исследованиях.…”
Section: цикламен в сравнении с плацебоunclassified
“…It is thought that 75% of patients with acute RS take antibiotics unnecessarily [3]. Clinical symptoms do not always indicate the necessity of antibiotics, and more reliable tools for an efficient RS diagnosis are still needed [4]. As part of the treatment, oral steroids, antihistamines, nasal irrigation, mucolytics, analgesics and local or systemic adrenergic decongestants are usually administered to suppress vascular circulation and gland secretion [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical trials have been carried out to assess herbal extract efficacy in RS patients. Cyclamen saponins freeze-dried extract reduces the symptoms of acute RS, restores muco-ciliary movements, and improves the rate of remission when compared to a placebo [4]. In these studies, the number of adverse effects was higher in the treatment group, mainly due to irritation at the treatment site.…”
Section: Introductionmentioning
confidence: 99%